2022
DOI: 10.1097/aog.0000000000004834
|View full text |Cite
|
Sign up to set email alerts
|

Racial Inequities in Breastfeeding Counseling Among Pregnant People Who Use Cannabis

Abstract: Pregnant non-Hispanic Black people are four times more likely than pregnant non-Hispanic White people to be advised against breastfeeding if using cannabis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…Counseling discouraging breastfeeding with concurrent marijuana use was more likely to be reported among individuals who were people of color, age 29 years or younger, with a high school education or less, unmarried, and reporting governmental or no insurance prepregnancy. These findings are consistent with other studies examining the demographics of people screened for marijuana use during pregnancy or postpartum 12,19,21,22 . Studies have shown that marijuana users are more likely to be younger (<25 years), unemployed, single, uninsured, non‐Hispanic Black, and with low income and education 23–25 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Counseling discouraging breastfeeding with concurrent marijuana use was more likely to be reported among individuals who were people of color, age 29 years or younger, with a high school education or less, unmarried, and reporting governmental or no insurance prepregnancy. These findings are consistent with other studies examining the demographics of people screened for marijuana use during pregnancy or postpartum 12,19,21,22 . Studies have shown that marijuana users are more likely to be younger (<25 years), unemployed, single, uninsured, non‐Hispanic Black, and with low income and education 23–25 .…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with other studies examining the demographics of people screened for marijuana use during pregnancy or postpartum. 12,19,21,22 Studies have shown that marijuana users are more likely to be younger (<25 years), unemployed, single, uninsured, non-Hispanic Black, and with low income and education. [23][24][25] According to the National Survey on Drug Use and Health from 2002 to 2019, the prevalence of marijuana use was highest among pregnant individuals aged 12 to 17 years (14.6%; 95% CI, 11.8-17.5) compared with those aged 18 to 25 years (7%; 95% CI, 6.3-7.8), and those aged 26 to 44 years (2.5%; 95% CI, 2.0-3.0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation